(untitled) (Proceedings of International Conference on Special Education, 2015)
This study aims to review the effectiveness of learning and teaching innovation special education (hearing) via video at the Polytechnic Tuanku Syed Sirajuddin, Polytechnic Special Skills Certificate (Hotel Catering) was implemented in June 2014 Semester. The sample was composed of 22 students from the Department of Tourism and Hospitality.These data are collected using a questionnaire instrument and analyzed using SPSS (statistical package for social sciences). Results of the analysis of data obtained in this study indicate that the level of understanding of special education students (hearing) at the Polytechnic Tuanku Syed Sirajuddin who teach special education students is moderate with a mean score. It is hoped that the findings of this study can serve as a guide to the management of Polytechnic Tuanku Syed Sirajuddin to evaluate the effectiveness of the video in the department involving lecturers in teaching special education students (hearing) and then take the help of various aspects of the role as described in the part of the proposal for enhance the delivery of teaching lessons to special education (hearing).